A preparation method of homogeneous lithium niobate piezoelectric coating, piezoelectric coating and application thereof

By applying an electric field with a negative potential difference between the substrate and the sputtering target, the particle flow is controlled, solving the problem of uneven morphology and performance in the preparation of LiNbO3 piezoelectric coatings, achieving improved uniformity and stability, and is suitable for Industrial production.

CN116732484BActive Publication Date: 2025-01-24WUHAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310595242.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2025-01-24
Estimated Expiration
2043-05-24

AI Technical Summary

Technical Problem

It is difficult to prepare a LiNbO3 piezoelectric coating with uniform morphology and performance in the prior art, and there are problems of cracks and lack of Li elements in the target preparation process, which affects the piezoelectric performance.

Method used

By applying an electric field with a negative potential difference between the substrate and the sputtering target, the running direction and energy of the particle flow are controlled, the formation of the wedge structure is reduced, and the escape of Li element is prevented. Homogeneous lithium niobate is prepared using magnetron sputtering technology. Piezoelectric coating.

Benefits of technology

The appearance and element distribution uniformity of the coating is realized, the uniformity and stability of the piezoelectric performance is improved, and it is suitable for industrialized large -scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116732484B_ABST
    Figure CN116732484B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method of a homogeneous lithium niobate piezoelectric coating, a piezoelectric coating and its application. The main body is a single-layer homogeneous lithium niobate piezoelectric coating, the coating elements are evenly distributed, the morphology structure and piezoelectric performance are not affected by the deposition position and the defects of the powder target material, and the sensing performance is uniform and excellent. In order to solve the problem of solid particles and element segregation, the present invention designs a particle flow control device, which adjusts the direction of the particle flow by setting a controllable and adjustable electric field between the substrate and the target material (the substrate potential is lower than the target material, and the potential difference is between 2V and 25V), so that the Ar + Bombarding solid particles reduces the formation of wedge-shaped structures, while accelerating gas phase particles to run to the substrate surface to prevent Li from escaping, and the obtained coating morphology, element distribution, and ultrasonic signal uniformity are better. The present invention is based on the ion flow energy and quantity control method, which is simple and efficient, does not require additional steps and costs, and is suitable for industrial mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of piezoelectric coating preparation, and in particular to a preparation method of a homogeneous lithium niobate piezoelectric coating, a piezoelectric coating and applications thereof. Background Art

[0002] Lithium niobate (LiNbO3) is a trigonal ferroelectric with good photorefractive effect, piezoelectric effect, thermoelectric effect, acousto-optic effect, electro-optic effect and nonlinear optical effect. It has a wide range of applications in holographic storage, piezoelectric sensors, thermoelectric sensors, acousto-optic modulators, electro-optic modulators, Q-switches in lasers, optical parametric oscillators, optical waveguides, etc.

[0003] LiNbO3 thin films are usually prepared by magnetron sputtering or pulsed laser deposition technology, which requires high-performance sputtering targets. LiNbO3 ceramic sputtering targets are usually prepared by pressing and sintering LiNbO3 and LiNb3O8 powders (or Nb2O5 and Li2CO3). Due to defects in the target preparation process, pure LiNbO3 and LiNb alloy targets cannot be directly obtained. In addition, due to the limited bonding force of the powder, the target is prone to cracks during high-temperature sputtering, causing the powder to fall directly onto the substrate, inducing the formation of a wedge-shaped structure, destroying the columnar crystals, and weakening the piezoelectric performance; at the same time, the Li element is light and active, and it is easy to form lithium-deficient phases NbO and Nb2O due to the lack of Li. 5、 LiNb3O8, again weakens the piezoelectric performance. Even if 5-10% of the Li element is added during the target material preparation process, it is difficult to obtain a single LiNbO3 phase with homogeneous morphology, elements and performance.

[0004] Therefore, it is necessary to prepare LiNbO3 piezoelectric coatings with uniform morphology and performance. Summary of the invention

[0005] In view of the technical problems existing in the prior art, one of the objects of the present invention is to provide a homogeneous lithium niobate piezoelectric coating, the main body of which is a single-layer homogeneous lithium niobate piezoelectric coating, the coating elements are evenly distributed, the morphology structure and piezoelectric properties are not affected by the deposition position and powder target defects, and the sensing performance is uniform and excellent.

[0006] The second object of the present invention is to provide a method for preparing a homogeneous lithium niobate piezoelectric coating, which is based on the ion flow energy and quantity control method, is simple and efficient, does not require additional steps and costs, and is suitable for industrial mass production.

[0007] In order to achieve the above object, the present invention provides a method for preparing a homogeneous lithium niobate piezoelectric coating, comprising the following steps:

[0008] Placing sputtering targets and substrates;

[0009] Then the magnetron sputtering parameters were adjusted;

[0010] Applying an electric field between the substrate and the target, and a negative potential difference exists between the substrate and the sputtering target;

[0011] The material of the sputtering target is deposited onto the substrate to form a homogeneous lithium niobate piezoelectric coating.

[0012] Furthermore, there is a negative potential difference between the substrate and the sputtering target, specifically,

[0013] The substrate potential is 2-25V lower than the sputtering target potential.

[0014] Furthermore, the intensity of the electric field is 0.2 to 5.5 V / cm.

[0015] Furthermore, the sputtering target is formed by mixing LiNbO3 powder, LiNb3O8 powder and Li2O powder and then pressing and sintering them.

[0016] Furthermore, the molar ratio of the LiNbO3 powder, the LiNb3O8 powder and the Li2O powder is between 10-3:10 and 3:1.

[0017] Furthermore, the magnetron sputtering parameters include radio frequency power, deposition gas pressure, flow ratio, deposition temperature, deposition time and target-substrate distance.

[0018] Preferably, the substrate comprises Si sheet, stainless steel sheet, WC, fasteners such as bolts and screws of different materials (30CrMnSiA and TC4, etc.), different structures (hexagonal head bolts, etc.), and different specifications (specifications 5-20, etc.).

[0019] Preferably, the homogeneous lithium niobate piezoelectric coating has consistent coating morphology, element distribution and ultrasonic signal within a radius of 8 cm.

[0020] Preferably, the radio frequency power is between 600W and 1200W.

[0021] Preferably, the deposition gas pressure is between 0.6Pa-4.0Pa.

[0022] Preferably, the flow ratio Ar / O2 is between 5 / 1 and 1 / 5.

[0023] Preferably, the deposition temperature is between 50 and 250°C.

[0024] Preferably, the target-base distance is between 2 cm and 10 cm.

[0025] Preferably, the deposition time is between 2 h and 10 h.

[0026] The present invention also provides a piezoelectric coating, which is prepared by the above-mentioned preparation method.

[0027] The present invention also provides the use of the homogeneous lithium niobate piezoelectric coating prepared by the above preparation method as a temperature sensor or a stress sensor.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention adds a controllable and adjustable electric field between the substrate and the target material to make Ar + Bombarding solid particles reduces the formation of wedge-shaped structures and accelerates the gas phase particles to run to the substrate surface to prevent Li from escaping, resulting in better coating morphology and element distribution uniformity.

[0030] 2. The homogeneous lithium niobate piezoelectric coating prepared by the present invention is completely homogeneous, and the ultrasonic signals that can be excited by the coating at various locations have excellent uniformity, consistent ultrasonic signals, and stable signal amplitudes, and no attenuation occurs after long-term annealing.

[0031] 3. The preparation method of the homogeneous lithium niobate coating of the present invention is based on the energy and quantity control method of ion flow (especially Ar, Li), which is simple and efficient, does not require additional steps and costs, and is suitable for industrial mass production.

[0032] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the steps or devices indicated in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 Schematic diagram of the formation mechanism of wedge-shaped structure and element segregation when the electric field control is not used in the comparative example of the present invention; wherein, Figure 1 (a) is a schematic diagram of forming a lithium niobate coating. Figure 1 (b) is a schematic diagram of solid particles falling on the lithium niobate coating. Figure 1 (c) is a schematic diagram of the divergent wedge-shaped structure. Figure 1 (d) is a schematic diagram of the generation of Li deficiency. Figure 1 (e) is a schematic diagram of the formation of O and Li element segregation;

[0035] Figure 2 Schematic diagram of the formation mechanism of a homogeneous coating when the electric field is used for control in the present invention, wherein: Figure 2 (a) is a schematic diagram of the structure of the particle flow control device. Figure 2 (b) is Ar + Schematic diagram of solid particles bombarding a substrate. Figure 2 (c) The solid particles are Ar + Schematic diagram of hitting and detaching the substrate;

[0036] FIG3 shows the morphology, element distribution, XRD and ultrasonic signal of the lithium niobate piezoelectric coating deposited in the comparative example of the present invention without using electric field control, wherein: Figure 3a This is the SEM image of the surface. Figure 3b is the element distribution diagram, Figure 3c This is a cross-sectional SEM image. Figure 3d is the XRD pattern, Figure 3e It is the ultrasound signal diagram;

[0037] FIG4 shows the morphology and element distribution of the homogeneous lithium niobate piezoelectric coating prepared when the potential difference is 20V in Example 1 of the present invention; wherein, Figure 4a This is the SEM image of the surface. Figure 4b This is a cross-sectional SEM image. Figure 4c is the element distribution diagram;

[0038] FIG5 is the morphology and XRD of the homogeneous lithium niobate piezoelectric coating prepared when the potential difference is 10V in Example 2 of the present invention; wherein, Figure 5a This is the SEM image of the surface. Figure 5b is the XRD pattern of the surface;

[0039] Figure 6 The ultrasonic signal of the homogeneous lithium niobate piezoelectric coating prepared in Example 3 of the present invention when the potential difference is 6V;

[0040] FIG. 7 shows the morphology and ultrasonic signal of the homogeneous lithium niobate piezoelectric coating prepared in Example 1 of the present invention after long-term annealing; wherein, Figure 7a This is the SEM image of the surface. Figure 7b It is the ultrasonic signal map of the surface;

[0041] Figure 8 is the ultrasonic signal of the homogeneous lithium niobate piezoelectric coating prepared at different temperatures in Example 4 of the present invention; wherein Figure 8 a is the ultrasonic signal obtained at a temperature of 80°C, Figure 8 b is the ultrasonic signal obtained at a temperature of 150°C, Figure 8 c is the ultrasonic signal obtained at a temperature of 200°C, Figure 8 d is the ultrasonic signal obtained at a temperature of 235°C;

[0042] Fig. 9This is a comparison diagram of the ultrasonic signal amplitude at the sputtering center and 4 cm away from the sputtering center of the homogeneous lithium niobate piezoelectric coating prepared at different temperatures in Example 4 of the present invention;

[0043] FIG10 is the morphology, XRD and ultrasonic signal of the lithium niobate piezoelectric coating prepared in Comparative Example 2 of the present invention when the potential difference is 30V; wherein, Fig.10a This is the SEM image of lithium niobate piezoelectric coating. Fig.10b is the XRD pattern of lithium niobate coating, Fig.10c This is the ultrasonic signal diagram of lithium niobate piezoelectric coating;

[0044] Fig.11 This is the XRD pattern of the surface of the homogeneous lithium niobate piezoelectric coating prepared when the potential difference is 6V in Example 5 of the present invention.

[0045] In the figure: 1-solid particles; 2-Li, Nb, O gas phase particle flow; 3-lithium niobate coating; 4-wedge structure; 5-edge of wedge structure; 6-Nb oxide; 7-Li element; 8-substrate; 9-lithium niobate target; 10-target bracket; 11-controllable and adjustable electric field; 12-Ar accelerated by bias voltage + ;13-heater. DETAILED DESCRIPTION

[0046] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0047] The preparation of LiNbO3 thin films based on magnetron sputtering technology requires high-performance sputtering targets. Due to the current limitations of target preparation processes, oxide ceramic targets made by sintering and pressing LiNbO3, LiNb3O8 powder and Li2O powder are usually used. This type of target has great disadvantages: Figure 1 Schematic diagram of the formation mechanism of wedge-shaped structure and element segregation when electric field control is not used. Figure 1 As shown in (a), solid particles 1, Li, Nb, O gas phase particle flow 2 are deposited to form a lithium niobate coating 3 with a columnar crystal structure; Figure 1 As shown in (b), solid particles 1 fall on lithium niobate coating 3. There are the following disadvantages in magnetron sputtering and coating deposition process:

[0048] Disadvantage 1: It is very easy to produce cracks on the target surface due to the combined effect of strong magnetic field and high temperature, such as Figure 1As shown in (c), the solid particles 1 generated in the target material are directly sputtered onto the substrate or the formed coating 3, inducing the formation of a divergent wedge-shaped structure 4, destroying the columnar crystal structure;

[0049] Disadvantage 2: Figure 1 As shown in (d), the Li element is very light. During the process from the target to the substrate, it is collided with other particles and cannot be smoothly deposited on the substrate, resulting in Li deficiency.

[0050] Disadvantage 3: Figure 1 As shown in (e), the Li element in the formed lithium niobate coating 3, especially the Li element 7 on the surface of the edge 5 of the wedge-shaped structure, is bombarded by the subsequent Li, Nb, and O particle flow 2, and continuously diffuses to the surroundings and is oxidized into Li2O, forming a segregation phenomenon of O and Li elements. At the same time, due to the lack of Li element, a large amount of Nb oxide 6 in the lithium-deficient phase exists inside the wedge-shaped structure.

[0051] For this reason, the design concept of the present invention is: Figure 2 As shown in (a), the present invention designs a particle flow control device. After the lithium niobate target 9 is placed on the target bracket 10, a controllable and adjustable electric field 11 is set between the substrate 8 and the lithium niobate target 9 (the potential of the substrate 8 is lower than that of the target 9, the potential difference is between 2V and 25V, and the electric field strength is between 0.2 and 5.5V / cm). The advantages are:

[0052] Advantage 1: The electric field 11 will control the direction of the particle flow, so that the Ar originally used to sputter the target and promote the target to generate coating raw materials + , not only maintaining the original function, but also accelerating through the bias voltage, under the action of the potential difference, bombarding the substrate with high speed and high energy like Li, Nb, and O particle flow 2, as primary ions (Ar + 12) bombarding the solid particles 1 (such as Figure 2 (b)), solid particles 1 are not grown on the substrate surface, and the bonding force between them and the substrate is low, so they are easily absorbed by Ar + Hitting off the substrate (such as Figure 2 (c)) weakens the formation of the wedge-shaped structure, which is conducive to the preparation of a piezoelectric coating with a uniform morphology and a columnar crystal structure, thus solving the above-mentioned disadvantages 1 and 3;

[0053] Advantage 2: At the same time, the potential difference will attract gas phase particles 12 such as Li, Nb, and O sputtered from the target material, reduce the divergent running trajectory, and make them run directly to the substrate, increasing the energy and number of atoms and atomic clusters (especially lightweight Li elements) reaching the substrate surface to promote coating deposition. At the same time, the electric field enhances the linearity and directionality of the particle flow, reduces collisions between particles, reduces the probability of Li element diffusion and escape, weakens the occurrence of lithium-deficient phases, and is conducive to the preparation of piezoelectric coatings with uniform elements and excellent columnar crystal structures in cross-section, solving the above-mentioned disadvantage 2.

[0054] Advantage 3: The particle flow control device also includes a heater 13, which is connected to the back of the sample holder and provides a stainless steel box with a resistive heating element. The heater is equipped with a thermocouple, which is set by a temperature controller and a power supply unit outside the vacuum chamber to control the temperature of the sample holder and the substrate. The temperature of the sample can be adjusted within the range of 100-500°C with an accuracy of 2°C. The heater 13 is placed directly behind the substrate 8, which is conducive to heating the sample at a close distance, removing impurities adsorbed on the surface of the substrate (such as H2O), and increasing the surface mobility of the deposited atoms, improving the uniformity of the elements, and promoting the formation of columnar crystals, which is conducive to improving the uniformity of the piezoelectric properties of the coating.

[0055] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the specific embodiments of the present invention and the accompanying drawings of the specification. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The substrates in the embodiments and comparative examples are Si sheets and stainless steel sheets, and deposition is performed on these two substrates respectively. When the substrate is a Si sheet, it is conducive to measuring morphology and elements, and when the substrate is stainless steel, it is convenient to measure piezoelectric signals.

[0056] Comparative Example 1

[0057] This comparative example proves that if there is no electric field between the substrate and the lithium niobate target, a piezoelectric coating with uneven morphology, elements, XRD, and ultrasonic signals is easily formed. A method for preparing a lithium niobate piezoelectric coating comprises the following steps:

[0058] Step 1, prepare the magnetron sputtering equipment, place the sputtering target and two substrates, Si wafer and stainless steel wafer;

[0059] Step 2: Set the RF power, deposition gas pressure, flow ratio, deposition temperature, deposition time and target-substrate distance to 900 W, 2.0 Pa, Ar / O2=2 / 1, 150°C, 8 h and 5 cm respectively, and deposit the material of the sputtering target onto the substrate to form a lithium niobate piezoelectric coating.

[0060] In the comparative example, the sputtering target was formed by mixing LiNbO3 powder, LiNb3O8 powder and Li2O powder in a molar ratio of 5:5:1 and then pressing and sintering.

[0061] Example 1

[0062] A method for preparing a homogeneous lithium niobate piezoelectric coating comprises the following steps:

[0063] Step 1, prepare the magnetron sputtering equipment, place the sputtering target and two substrates, Si wafer and stainless steel wafer;

[0064] Step 2, setting the RF power, deposition pressure, flow ratio, deposition temperature, deposition time and target-substrate distance to 900 W, 2.0 Pa, Ar / O2=2 / 1, 150°C, 8 h and 5 cm respectively;

[0065] Step 3, applying an electric field of 4 V / cm between the substrate and the target, wherein the potential of the substrate is 20 V lower than the potential of the sputtering target;

[0066] Step 4: Deposit the sputtering target material onto the substrate to form a homogeneous lithium niobate piezoelectric coating

[0067] In Example 1, the sputtering target is formed by mixing LiNbO3 powder, LiNb3O8 powder and Li2O powder in a molar ratio of 5:5:1 and then pressing and sintering.

[0068] Example 2

[0069] A method for preparing a homogeneous lithium niobate piezoelectric coating comprises the following steps:

[0070] Step 1, prepare the magnetron sputtering equipment, place the sputtering target and two substrates, Si wafer and stainless steel wafer;

[0071] Step 2: Set the RF power, deposition pressure, flow ratio, deposition temperature, deposition time and target-substrate distance to 900 W, 2.0 Pa, Ar / O2=2 / 1, 150°C, 8 h and 5 cm, respectively.

[0072] Step 3, applying an electric field of 2 V / cm between the substrate and the target, wherein the potential of the substrate is 10 V lower than the potential of the sputtering target;

[0073] Step 4: deposit the sputtering target material onto the substrate to form a homogeneous lithium niobate piezoelectric coating.

[0074] In Example 2, the sputtering target is formed by mixing LiNbO3 powder, LiNb3O8 powder and Li2O powder in a molar ratio of 5:5:1 and then pressing and sintering.

[0075] Example 3

[0076] A method for preparing a homogeneous lithium niobate piezoelectric coating comprises the following steps:

[0077] Step 1, prepare the magnetron sputtering equipment, place the sputtering target and two substrates, Si wafer and stainless steel wafer;

[0078] Step 2, setting the RF power, deposition pressure, flow ratio, deposition temperature, deposition time and target-substrate distance to 900 W, 2.0 Pa, Ar / O2=2 / 1, 150°C, 8 h and 5 cm respectively;

[0079] Step 3, applying an electric field of 1.2 V / cm between the substrate and the target, wherein the potential of the substrate is 6 V lower than the potential of the sputtering target;

[0080] Step 4: deposit the sputtering target material onto the substrate to form a homogeneous lithium niobate piezoelectric coating.

[0081] In Example 3, the sputtering target is formed by mixing LiNbO3 powder, LiNb3O8 powder and Li2O powder in a molar ratio of 5:5:1 and then pressing and sintering.

[0082] Example 4

[0083] A method for preparing a homogeneous lithium niobate piezoelectric coating comprises the following steps:

[0084] Step 1, prepare the magnetron sputtering equipment, place the sputtering target and two substrates, Si wafer and stainless steel wafer;

[0085] Step 2, setting the RF power, deposition pressure, flow ratio, deposition time and target-substrate distance to 900 W, 2.0 Pa, Ar / O2=2 / 1, 8 h and 5 cm respectively;

[0086] Step 3, turn on the heater behind the substrate and set it to 80°C, 150°C, 200°C, and 235°C in sequence;

[0087] Step 4: deposit the material of the sputtering target onto the substrate to form a lithium niobate piezoelectric coating.

[0088] In Example 4, the sputtering target is formed by mixing LiNbO3 powder, LiNb3O8 powder and Li2O powder in a molar ratio of 5:5:1 and then pressing and sintering.

[0089] Comparative Example 2

[0090] This comparative example is used to prove that the potential difference of the controllable and adjustable electric field between the substrate and the lithium niobate target is between 2V and 25V, and the electric field strength is between 0.2 and 5.5V / cm. Too high an electric field strength will damage the coating morphology, XRD orientation and weaken the piezoelectric signal. The following steps are included:

[0091] Step 1, prepare the magnetron sputtering equipment, place the sputtering target and two substrates, Si wafer and stainless steel wafer;

[0092] Step 2, setting the RF power, deposition pressure, flow ratio, deposition temperature, deposition time and target-substrate distance to 900 W, 2.0 Pa, Ar / O2=2 / 1, 150°C, 8 h and 5 cm respectively;

[0093] Step 3, applying an electric field of 6 V / cm between the substrate and the target, wherein the potential of the substrate is 30 V lower than the potential of the sputtering target;

[0094] Step 4: deposit the material of the sputtering target onto the substrate to form a lithium niobate piezoelectric coating.

[0095] In Comparative Example 2, the sputtering target is formed by mixing LiNbO3 powder, LiNb3O8 powder and Li2O powder in a molar ratio of 5:5:1 and then pressing and sintering.

[0096] Example 5

[0097] This embodiment is to prove that based on the above-mentioned "the potential difference of the controllable and adjustable electric field between the substrate and the lithium niobate target is between 2V and 25V, and the electric field strength is between 0.2 and 5.5V / cm", as long as the voltage and the electric field are within the above range, the RF power, deposition pressure, flow ratio, deposition temperature, deposition time and target-substrate distance can still be adjusted to obtain a homogeneous lithium niobate piezoelectric coating. This embodiment takes changing the deposition pressure as an example, and includes the following steps:

[0098] Step 1, prepare the magnetron sputtering equipment, place the sputtering target and two substrates, Si wafer and stainless steel wafer;

[0099] Step 2, setting the RF power, deposition pressure, flow ratio, deposition temperature, deposition time and target-substrate distance to 900 W, 1.0 Pa, Ar / O2=2 / 1, 150°C, 8 h and 5 cm respectively;

[0100] Step 3, applying an electric field of 1.2 V / cm between the substrate and the target, wherein the potential of the substrate is 6 V lower than the potential of the sputtering target;

[0101] Step 4: deposit the material of the sputtering target onto the substrate to form a lithium niobate piezoelectric coating.

[0102] In Example 5, the sputtering target is formed by mixing LiNbO3 powder, LiNb3O8 powder and Li2O powder in a molar ratio of 5:5:1 and then pressing and sintering.

[0103] Test Case

[0104] Note: For the stacked graph of ultrasonic signals and XRD experimental data of multiple sample tests, only part of the curve is shifted upwards, and the signal amplitude of the ultrasonic signal depends on (maximum value of the vertical coordinate of the curve - minimum value of the vertical coordinate of the curve) / 2.

[0105] The morphology, element distribution, crystal structure and ultrasonic signal of the lithium niobate piezoelectric coating prepared in the comparative example were measured by SEM, EDS, XRD and ultrasonic equipment. Figure 3a From the SEM image of the surface 4 cm away from the sputtering center, it can be seen that a non-spherical corrugated surface morphology is formed, and the morphology is uneven. Figure 3b The EDS image at 4 cm from the sputtering center shows that the surface elements are unevenly distributed, and the peaks of the ripples are rich in oxygen, indicating that there is Li segregation (Li is oxidized to Li2O). Figure 3c From the SEM image of the cross section 4 cm away from the sputtering center, it can be seen that the cross section is a wedge-shaped structure and is relatively loose, not a columnar crystal structure. Figure 3d The XRD patterns at the sputtering center and 4 cm away from the sputtering center show that the coating formed at the center of the sputtering area contains not only LiNbO3, but also NbO and Nb2O5, while the coating away from the sputtering center contains almost no LiNbO3 and is mainly lithium-deficient NbO and Nb2O5. Figure 3e It can be seen from the ultrasonic signal test results at 0cm and 4cm away from the sputtering center that the signal amplitude at the sputtering center is much higher than that at 4cm away from the sputtering center, indicating that the lithium-deficient phase seriously affects the excitation of the ultrasonic signal.

[0106] The morphology of the homogeneous lithium niobate piezoelectric coating prepared in Example 1 was measured using SEM. Figure 4a From left to right, SEM images of the coating surface at 0 cm, 1 cm, 2 cm, and 4 cm from the sputtering center are shown respectively; it can be seen that under the action of a 4 V / cm electric field (the substrate potential is 20 V lower than the sputtering target potential), a uniform structure is formed on the coating surface, and the grain morphology and size are completely consistent; Figure 4b From left to right, SEM images of the coating cross-sections at 0 cm, 1 cm, 2 cm, and 4 cm from the sputtering center are shown respectively. It can be seen that the cross-section has a uniform morphology of pure columnar crystals.

[0107] Figure 4c The EDS Mapping diagram of the surface of the homogeneous lithium niobate piezoelectric coating prepared in Example 1 at 4 cm from the sputtering center is shown, indicating that the surface elements of the homogeneous lithium niobate piezoelectric coating at 4 cm from the sputtering center are still evenly distributed, and there is no oxygen-rich area and Li element segregation problem.

[0108] Figure 5aA low-magnification SEM image of the surface of the homogeneous lithium niobate piezoelectric coating prepared in Example 2 is shown. It can be seen that under the action of a 2V / cm electric field (the substrate potential is 10V lower than the sputtering target potential), the lithium niobate coating formed in a large area of ​​the surface has an extremely uniform morphology, with only grains present without any ripples formed. Figure 5b The XRD patterns of the homogeneous lithium niobate piezoelectric coating prepared in Example 2 at 0 cm and 4 cm from the sputtering center are shown. It can be seen that the coating at the sputtering center and the coating 4 cm away from the sputtering center (including the left and right sides) have completely consistent XRD structures in crystal structure and crystal orientation, mainly containing LiNbO3, without NbO, which greatly reduces the formation of lithium-deficient phase.

[0109] Figure 6 The ultrasonic signal test results of the homogeneous lithium niobate piezoelectric coating prepared in Example 3 at 0cm, 2cm and 4cm from the sputtering center are shown. It can be seen that under the action of a 1.2V / cm electric field (the substrate potential is 6V lower than the sputtering target potential), the ultrasonic signal that can be excited by the coating at each location has excellent uniformity, consistent signal amplitude and high signal-to-noise ratio. Two waveforms, transverse waves and longitudinal waves, appeared 4cm away from the sputtering center. The reason is that the coating at this location has inclined columnar crystals, which promotes the generation of transverse waves; while below 4cm, the columnar crystals of the coating have better verticality and will generate a single longitudinal wave. This means that in addition to changing the deposition parameters, the required wave type can also be generated by regulating the lateral distance. The controllable and adjustable nature of pure longitudinal waves and longitudinal-transverse dual waves is conducive to the use of a single wave method to measure the preload of fasteners, the use of a dual wave method to measure the axial force of fasteners online, and the use of a sound-time method to measure the temperature distribution of fasteners, turbine blades, etc. in real time. (In the figure, L represents longitudinal waves and S represents transverse waves)

[0110] The high temperature stability of the coating is also an important indicator of the coating properties. The homogeneous lithium niobate piezoelectric coating prepared in Example 1 was annealed at 700°C for 5, 10, 20, 40, 60, 80 and 100 hours, and the morphology and the stability of the ultrasonic signal were measured using SEM and ultrasonic equipment. Figure 7a From the SEM image of the homogeneous lithium niobate piezoelectric coating after annealing at 700℃, it can be seen that during the annealing period of 700℃ for 5 to 100h, the coating morphology, grain shape and size are no different from those before high temperature treatment; Figure 7b The ultrasonic signal diagram of the homogeneous lithium niobate piezoelectric coating after annealing at 700°C for 100h shows that the signal amplitude is stable, the signal-to-noise ratio is high, and there is no attenuation. It can be seen that the homogeneous lithium niobate piezoelectric coating prepared by the technology of the present invention not only suppresses the formation of wedge-shaped structure and lithium-deficient phase, and obtains uniform distribution of coating morphology and elements, but also has excellent uniformity and high-temperature stability of ultrasonic waves excited by the coating.

[0111] Figure 8 (a) Figure 8(b) Figure 8 (c) and Figure 8 (d) shows the ultrasonic signal test results of the homogeneous lithium niobate piezoelectric coating prepared in Example 4 at 80°C, 150°C, 200°C, and 235°C, respectively. Fig. 9 These results are summarized in Fig. 9 It can be seen that when the temperature is below 200°C, the ultrasonic signal at the edge of the sputtering area is much lower than that at the center of the sputtering area. When heated to 235°C, the signals at the sputtering edge and the sputtering center are equal, and a lithium niobate piezoelectric material with uniform piezoelectric signals is obtained. The heater behind the substrate improves the uniformity of the coating well.

[0112] Fig.10a , Fig.10b , Fig.10c The morphology, XRD, and ultrasonic signal data of the lithium niobate coating prepared in Comparative Example 2 at a bias voltage of 30 V and an electric field of 6 V / cm are respectively shown. Fig.10a The SEM morphology measurement results show that the grain size of the lithium niobate surface prepared under this bias condition is uneven and severely corroded, with large pits up to 60×130μm in size. Obvious interface detachment cracks can be seen on the end face, and the non-detached part does not have a good columnar crystal structure. Fig.10b The XRD crystal structure measurement results show that lithium-deficient NbO and Nb2O5 phases appear under this bias condition, indicating that the element distribution is not uniform. Fig.10c The ultrasonic signal measurement results show that the ultrasonic signal of lithium niobate prepared under this bias condition is extremely weak and has a low signal-to-noise ratio. The signal amplitude is only 2% of that under the bias conditions of 20V and 6V. Therefore, the lithium niobate coating prepared under the bias of 30V and the electric field of 6V / cm does not have good uniformity. These results show that too high a bias will destroy the coating morphology, XRD orientation and weaken the piezoelectric signal.

[0113] Fig.11 The XRD patterns of the homogeneous lithium niobate piezoelectric coating prepared in Example 5 at 0cm and 4cm from the sputtering center are shown, indicating that when the deposition pressure is reduced to 1.0Pa, it can still be seen that the coating at the sputtering center and 4cm away from the sputtering center have completely consistent XRD structures in crystal structure and crystal orientation, mainly containing LiNbO3, without NbO, which greatly reduces the formation of lithium-deficient phase. It is proved that as long as the potential difference of the controllable and adjustable electric field between the substrate and the lithium niobate target is between 2V and 25V, and the electric field strength is between 0.2 and 5.5V / cm, the RF power, deposition pressure, flow ratio, deposition temperature, deposition time and target-base distance can be adjusted, and a homogeneous lithium niobate piezoelectric coating can still be obtained.

[0114] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a homogeneous lithium niobate piezoelectric coating, characterized in that: include, Placing sputtering targets and substrates; Then the magnetron sputtering parameters were adjusted; Applying an electric field between the substrate and the target, and a negative potential difference exists between the substrate and the sputtering target; Depositing the material of the sputtering target onto the substrate to form a homogeneous lithium niobate piezoelectric coating; The substrate potential is 2-25V lower than the sputtering target potential; The intensity of the electric field is 0.2~5.5V / cm; The sputtering target is formed by mixing LiNbO3 powder, LiNb3O8 powder and Li2O powder and then pressing and sintering, and the molar ratio of the LiNbO3 powder, the LiNb3O8 powder and the Li2O powder is between 10~3:10~3:1; The magnetron sputtering parameters include radio frequency power, deposition gas pressure, flow ratio, deposition temperature, deposition time and target-substrate distance; The deposition pressure is between 0.6Pa and 4.0Pa; The flow ratio Ar / O2 is between 5 / 1 and 1 / 5; The radio frequency power is between 600W and 1200W.

2. The preparation method according to claim 1, characterized in that: The deposition temperature is between 50 and 250° C. The target-base distance is between 2 cm and 10 cm; The deposition time is between 2h and 10h.

3. A piezoelectric coating, characterized in that: The preparation method is described in claim 1 or 2.

4. Application of the homogeneous lithium niobate piezoelectric coating prepared by the preparation method according to claim 1 or 2 as a temperature sensor or a stress sensor.

Citation Information

Patent Citations

  • Preparation method of piezoelectric coating with adjustable surface morphology and piezoelectric coating

    CN114752903A